Spectrum of interstitial lung diseases and their association with pulmonary hypertension - Tyagi, Richa; Kant, Surya; Verma, Sanjeev Kumar; Kushwaha, Ram Awadh Singh; Kumar, Santosh; Garg, Rajiv; Verma, Ajay Kumar; Srivastava, Anand; Bajaj, Darshan Kumar; Wakhlu, Anupam; Parihar, Anit; Pradhan, Akshyaya; et al. (Monaldi Archives for Chest Disease, 2021)
Interstitial lung diseases (ILDs) are an intriguing group of pulmonary disorders, which still require the study of epidemiological, genetic, pathophysiological, clinical, and radiological parameters. Pulmonary hypertension (PH) is an underreported complication in interstitial lung diseases which is associated with worse outcome. In our study, we have reported the spectrum of ILDs and estimated the prevalence of pulmonary hypertension among these subjects at a tertiary care centre. A cross-sectional study was performed in which demographical, clinical, radiological, and histological data of subjects with ILD, attending the department of Respiratory Medicine in the University was collected from 1st September 2018 to 31st August 2019. Serological tests were done wherever indicated. Standard criteria along with multidisciplinary opinion were needed to arrive at the final diagnosis. All subjects were screened for pulmonary hypertension via 2-D echocardiography. Mean pulmonary artery pressure ≥20 mmHg was used to define PH. In the defined period, 239 subjects were enrolled (58% females, n=141; mean age 52.38±13.40 years). A tissue diagnosis was obtained in 34% cases. The most common ILD was hypersensitivity pneumonitis (32.2%), followed by autoimmune-ILD (31.4%), idiopathic pulmonary fibrosis (IPF) (15.9%) and sarcoidosis (12.6%), non-IPF idiopathic interstitial pneumonitis (2.1%) and rest 21 (5.9%) subjects were diagnosed as other types of ILD. Pulmonary hypertension was seen in 46.0% of subjects.